Development of Android-Based Media in Support of Birth Planning and Complications Prevention Programs - Murdiningsih; Rohaya; Siti Hindun; Ida Mardalena (International Journal Scientific and Professional (IJ-ChiProf), 2022)
In Indonesia, AKI and AKB until now are still high, related to the problem of pregnancy, childbirth, and postpartum based on data released by the Ministry of Health, among others: AKI amounting to 305/100.000 live births. AKB (Neonate 15/1000 Live births and 24/1000 live births( KLH) in 2018 (Kemenkes, RI 2018). AKI in South Sumatra Province in 2015 amounted to 165/100,000 KH. AKI is one of the indicators of the degree of health of a country that shows the ability and quality of health services. The high AKI and the slow decline of this figure show that maternal and child health services (KIA) urgently need to be the main priority in terms of reach and quality of service. Maternal mortality is caused by multiple factors, which result from the interaction of various aspects, both clinical elements, parts of the healthcare system, and non-health factors that affect the delivery of clinical services and the optimal implementation of the healthcare system. The dominant aspects of maternal mortality in 2017 were bleeding in 37 cases, hypertension in pregnancy at 35 points, and 21 issues due to other factors (Dinkes Prov. Sumsel, 2017). First aid is a breakthrough effort to accelerate the decline in maternal and newborn mortality through activities to improve access and quality of care, as well as an exercise to build community potential, especially community concern for preparation and action in saving mothers and newborns through pregnancy, childbirth and postpartum (Ministry of Health, 2009 in Putri Andanawarih, 2018). One of the efforts to reduce AKI due to complications of pregnancy and birth is through first aid. First aid includes recording pregnant women, savings of pregnant women, preparation of prospective blood donors, family roles, helper plans, transportation to health facilities, and stamping stickers in the built house. At the Palembang City Health Center, the Purpose of The Research is to discover the "Development of Android-Based Health Promotion Methods in implementing the Birth Planning and Complication Prevention (P4k) Program of Palembang city and Jogyakarta in 2021". Benefits are expected as input to take a policy in applying first aid in Palembang City. The type of research carried out is Analytical research with experimental research design, which is where independent variables (Knowledge and attitudes) and dependent variables (Behavioral Changes in the Application of Childbirth Planning and Prevention of Complications (P4K). The study results showed a significant difference in maternal knowledge and attitudes before and after intervention giving health promotion through android applications with first aid with a value of 0.00 (<α0.05) and no association in the Control group. As for the distinct group of mothers, the most dominant case group is maternal education which can affect behavior changes. It is recommended that health workers should continue to improve information communication and education to pregnant women and conduct counseling and health promotion activities for the public. Health workers for education related to first aid and readiness to face childbirth complications.